SHORT NOTICES - Brooke, George J. (Journal of Semitic studies, 2003)
On Scrolls, Artefacts and Intellectual Property (Journal for the Study of the Pseudepigrapha Supplement Series 38) Timothy H. Lim, Hector L. Macqueen and Calum M. Carmichael (eds), Sheffield Academic Press, Sheffield 2001. Pp. 269. Price: £50.00 hardback. ISBN: 1-84127-212-4.